Design an arch footbridge / Khairunnisa Muhamad - Muhamad, Khairunnisa (2006)
In recent year’s bridge construction have been the most popular issues in structural engineering design and construction among engineers. Bridge constructions are the symbol of mankind’s conquest of space. The analysis and design of an arch footbridge was studied in this project. An arch footbridge was chosen because arches have a specific shape that allows them to carry loads primarily in a state of pure compression for one specific arrangement of loads. Besides that the arch itself has its own aesthetic values of the bridge. In this project the bridge was designed for 50 meter length of span, 3 meter width of deck and 15 meter rise of the arch crown. The designed of this bridge covered the deck, beam, trusses cable and connection analysis and design. Beam and deck was designed as reinforce concrete design while others as steel designed. The variable loads imposed the bridge only from pedestrians’ loadings and wind loading. The behaviours of the structure that have been considered are the deflection and flexural (axial forces, shear forces and bending moment) of the structure. The flexural behaviours was analysed by using 2-Dimensional simulation in LUSAS. The deflection and deformed mesh is analysed by using 3-Dimensional simulation of LUSAS. The final deflection of the bridge structure in this final year project is 0.1749 meter which satisfied the permissible deflection for 50 meter lengths of bridge span which is 0.25 meter.